Mucin 1 as a Molecular Target of a Novel Diisoquinoline Derivative Combined with Anti-MUC1 Antibody in AGS Gastric Cancer Cells - Agnieszka Gornowicz (MDPI AG, 2021)
Background: The aim of the study was to examine the molecular mechanism of the anticancer action of a monoclonal antibody against MUC1 and a diisoquinoline derivative (OM-86II) in human gastric cancer cells. Methods: The cell viability was measured by the MTT assay. The disruption of mitochondrial membrane potential and activity of caspase-8 and caspase-9 was performed by flow cytometry. Fluorescent microscopy was used to confirm the proapoptotic effect of compounds. LC3A, LC3B and Beclin-1 concentrations were analyzed to check the influence of the compounds on induction of autophagy. ELISA assessments were performed to measure the concentration of mTOR, sICAM1, MMP-2, MMP-9 and pro-apoptotic Bax. Results: The anti-MUC1 antibody with the diisoquinoline derivative (OM-86II) significantly reduced gastric cancer cells’ viability. This was accompanied by an increase in caspase-8 and caspase-9 activity as well as high concentrations of pro-apoptotic Bax. We also proved that the anti-MUC1 antibody with OM-86II decreased the concentrations of MMP-9, sICAM1 and mTOR in gastric cancer cells. After 48 h of incubation with such a combination, we observed higher levels of the crucial component of autophagosomes (LC3) and Beclin-1. Conclusions: Our study proved that the anti-MUC1 antibody sensitizes human gastric cancer cells to the novel diisoquinoline derivative (OM-86II) via induction of apoptosis and autophagy, and inhibition of selected proteins such as mTOR, sICAM1 and MMP-9.